Monitoring and Evaluation Systems and Performance of Local Governments: A Case of Nakapiripirit District - Immaculate Maruk (Uganda Christian University, 2024)
The study investigated the relationship between Monitoring and Evaluation systems and performance of local governments in Nakapiripirit District of Eastern Uganda. Specifically, the study focused on establishing the relationship between M&E systems inputs, M&E systems process, M&E systems outputs and performance of local governments in Nakapiripirit District. The study used a cross sectional study design employing both qualitative and quantitative research approaches. The population (112) of the study consisted of the Town clerks, Political leaders and Town council employees to which simple random sampling was applied. Quantitative data was collected from a sample of 86 respondents using researcher administered questionnaire. Responses were rated on a 5-Likert scale and analyzed for descriptive and inferential statistic using SPSS software presented in tables. Qualitative data was collected from 11 key informants using interview guides analyzed using content analysis and presented as text. Correlational analysis revealed that a significant and a strong positive linear relationship between performance of local governments in Nakapiripirit District and M&E systems inputs (r= 0.730**, p < 0.05), M&E system process (r= 0.814**, p < 0.05) and M&E system outputs (r= 0.739**, p < 0.05). Regression analysis showed a significant and positive influence of M&E system inputs (β=-.203, p=.001, <0.05), M&E system process (β=.071, p=.001, <0.05) and M&E system outputs (β=.315, p=.000, <0.05) on the performance of local governments in Nakapiripirit District. There are weaknesses in the M&E systems in local governments in Nakapiripirit District in terms of failure to track results despite the huge investments in area of M&E. Therefore, there is need to strengthen the M&E systems of local governments in Nakapiripirit district by; placing trained M&E human resource; developing M&E frameworks and developing costed M&E work plans Future studies should examine the perception of local government employees on the institutionalization of M&E system in the public sector of Uganda.
Undergraduate research